2019
DOI: 10.1111/jocn.14764
|View full text |Cite
|
Sign up to set email alerts
|

Surgical patients’ experiences of readiness for hospital discharge and perceived quality of discharge teaching in acute care hospitals

Abstract: Aims and objectives To examine the level of perception of the quality of discharge teaching and its associations with the readiness for hospital discharge among surgical patients in acute care hospitals. Background Discharge teaching is a primary strategy to facilitate patients’ readiness for hospital discharge. The extent to which the surgical ward was perceived as providing patient‐focused education when discharged has never been explored. Its impact on a patient's readiness is also unknown in the Indonesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
2
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 18 publications
8
54
2
11
Order By: Relevance
“…This study showed that the length of stay is another independent factor of discharge readiness, which is consistent with evidence from previous studies (Kaya, et al., 2018; Nurhayati et al., 2019; Weiss et al., 2004). Patients who were hospitalized for 10–20 days (OR = 2.340) or less than 10 days (OR = 2.803) were more likely to be ready for discharge than patients who were hospitalized for more than 20 days in this study.…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that the length of stay is another independent factor of discharge readiness, which is consistent with evidence from previous studies (Kaya, et al., 2018; Nurhayati et al., 2019; Weiss et al., 2004). Patients who were hospitalized for 10–20 days (OR = 2.340) or less than 10 days (OR = 2.803) were more likely to be ready for discharge than patients who were hospitalized for more than 20 days in this study.…”
Section: Discussionsupporting
confidence: 93%
“…15 Any disagreements were adjudicated by a third author. Since the number of questions on each checklist varied, [8][9][10][11][12][13] the final scores were calculated as a percentage to allow for crossstudy comparison. A minimum score of 50% was set as a level of quality for the study to be included in the quantitative analysis.…”
Section: Risk Of Bias Assessment (Quality Appraisal)mentioning
confidence: 99%
“…There is no widely accepted definition of caregiver readiness ; however, it has been described as incorporating four stages, precontemplation, contemplation, preparation and action . It can also be influenced by other factors such as personal, physical and emotional . The caregiver and patients’ ability to cope with the transition home encompasses their level of function and the caregiver's ability to manage worry, handle demands and carry out the required aspects of assistance .…”
Section: Introductionmentioning
confidence: 99%
“…Для об'єктивності готовність до виписки виражалась у числовому форматі через шкалу післяопераційної готовності до виписки PT-RHDS (частіше відому як READI) [11]. Як і в попередніх дослідженнях наших колег в оцінці за READI задовільним вважався показник вище 7 балів, хорошим -вище 9 [12,13].…”
Section: вступunclassified